Development of an urban molecular xenomonitoring system for lymphatic filariasis in the Recife Metropolitan Region, Brazil - Ramesh, Anita (2018)
Fundação Oswaldo Cruz. Instituto Aggeu Magalhães. Departamento de Parasitologia. Recife, PE, Brasil / London School of Hygiene & Tropical Medicine (LSHTM). Department of Infectious Disease Epidemiology. London, United Kingdom.